Assessing and comparing knowledge, attitude, and practices related to water, sanitation and hygiene among government and non-government school students in Gujarat: a mixed method study - Monika Patel; Eshwar Kumar Gupta; M. Yogesh (BMC Public Health)
Abstract Background Water, sanitation, and hygiene (WASH) practices are vital for health, especially among school students who can propagate messages. Comparing WASH knowledge, attitudes and practices between government and non-government schools can guide tailored interventions. This study aimed to assess and compare WASH-related knowledge, attitudes, and practices among adolescents in government versus non-government schools in Gujarat, India. Materials and methods A cross-sectional survey was conducted among 566 students from 17 government and 17 non-government schools. Interviews using a standardized questionnaire provided quantitative data on WASH-related knowledge, attitudes, and practices. Qualitative data was gathered through focus group discussions exploring influences on student WASH behaviors. Analyses included descriptive statistics, group comparisons, multivariate regression, and thematic analysis. A value of P < 0.05 was considered significant. Results In total, 566 students participated, with 257 (45%) from government and 309 (55%) from non-government schools. Non-government students showed significantly better knowledge of handwashing (AOR 1.9, 95% CI 1.3–2.7), fecal-oral transmission (AOR 1.8, 95% CI 1.3–2.5), open defecation (AOR 1.7, 95% CI 1.2–2.4), and menstrual hygiene (AOR 3.2, 95% CI 1.1–9.2). More non-government students had positive attitudes about safe drinking water (AOR 4.1, 95% CI 1.8–9.6), conserving water (AOR 2.0, 95% CI 1.4–2.9), cleanliness (AOR 1.8, 95% CI 1.1–2.9), investing in hygiene (AOR 5.3, 95% CI 3.1–9.2), and menstrual management (AOR 2.1, 95% CI 1.2–3.6). In practices, non-government students showed higher use of soap (AOR 1.9, 95% CI 1.3–2.8), better menstrual hygiene (AOR 5.9, 95% CI 3.2–10.9), and more sanitary defecation (AOR 2.7, 95% CI 1.8-4.0). Superior WASH outcomes were associated with older age (AOR 1.8, 95% CI 1.1-3.0), urban locality (AOR 2.3, 95% CI 1.5–3.5), higher parental education (AOR 2.1, 95% CI 1.3–3.4), and affluence (AOR 3.1, 95% CI 1.8–5.2). Qualitative data highlighted knowledge gaps, inadequate facilities, detrimental cultural beliefs, poverty, and the need for government support. Conclusions Disparities exist in WASH behaviors between school types, suggesting the need for tailored interventions addressing specific gaps. Schools play a critical role in cultivating proper hygiene through infrastructure provision and targeted education. Government schools may require extra support to overcome challenges related to WASH access and quality.